EVALUASI DAMPAK KEBIJAKAN PROGRAM PEMBERDAYAAN PEREMPUAN PENGEMBANG EKONOMI LOKAL (P3EL) DI KABUPATEN SIDOARJO - Sri Wibawani; Fadiyah Suci Rahmadini; Safitri Nur Laili (Universitas Halu Oleo, 2021)
Poverty is one example of a social problem that almost occurs throughout the world. In fact, it is not uncommon for the problem of poverty to cause various other social problems. In a developing country like Indonesia, the problem of poverty is the main problem that is still being pursued to minimize the poverty rate with programs that have been made by the government. Coupled with the emergence of the Covid-19 pandemic that is happening right now will greatly affect the economic level of the community. To overcome the problem of poverty that occurs, the Sidoarjo Regency government has made various ways to tackle poverty with various programs. One of the programs made by the Sidoarjo Regency government is the Local Economic Development Women Empowerment Program (P3EL). This program is an empowerment program intended for women in order to increase income for family welfare. Therefore, this study aims to determine the impact of the Local Economic Development Women Empowerment Program (P3EL) in Sidoarjo Regency. This study uses a descriptive research methodology with a qualitative approach. With the P3EL activity, it is hoped that business groups managed by women will grow and develop that are rational, economic, independent, equal and able to partner with other existing economic institutions.